Pengalaman Perawat yang Tidak Merawat Pasien COVID-19 di Rumah Sakit Kota Medan - Tina Rahayu Silitonga; Mula Tarigan (Jurnal Berita Ilmu Keperawatan, 2022)
Coronavirus disease 2019 (COVID-19) is a new variant of disease which has never been identified in human beings and is a communicable respiratory tract disease, it is very harmful to people, especially to nurses since not all healthcare workers in a hospital are equipped with Personal Protective Equipment (PPE) due to its limited availability in Indonesia. The objective of the research is to explore the experience of nurses who do not take care of patients COVID-19 patients in a hospital during COVID-19 pandemic. The research employs qualitative method with descriptive phenomenological approach. The participants are 10 nurses who do not take care of COVID-19 patients at USU hospital, selected by nursing purposive sampling technique. The data are collected through in-depth interviews. All interviews are firstly recorded and then transcribed. They are analyzed by using Colaizzi test approach. The result of the thematic analysis finals six themes: that the nurses have psychological impact, have COVID-19 pandemic impact, encounter obstacles during the pandemic, carry out coping mechanism, develop strategies in handling COVID-19, and receive social support. It is concluded that nurses experience psychological impact in the beginning of the pandemic such as excessive anxiety and stress so that they need social support from families, colleagues, or neighbors. The nurses knowledge of COVID-19 is still poor, so that it is necessary to provide more profound seminars and training.